2020
DOI: 10.1002/joc.6732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tropical North Atlantic sea surface temperature on intense tropical cyclones landfalling in China

Abstract: This study identifies a significant positive association between tropical North Atlantic (TNA) sea surface temperature (SST) during preceding spring and the frequency of intense tropical cyclones (TCs) making landfall over mainland China during autumn on interannual time scales. Observational analyses show that a warm SST anomaly in TNA during spring can induce a warm SST anomaly in the western part of the western North Pacific (WNP) in subsequent autumn, through a chain of air‐sea coupled processes such as Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Madden-Julian oscillation (MJO), Pacific-Japan (PJ) teleconnection and other atmospheric variabilities also play roles in influencing the WNP TC activity (Nakazawa 1986;Maloney and Hartmann 2001;Wu et al, 2020;Zhou et al, 2019). Some other studies highlighted the remote effects of SST variability in Indian and Atlantic Oceans on WNP TCs but mostly focused on the frequency and genesis of TCs (Liu and Chan, 2008;Liu and Chan, 2013;Huo et al, 2015;Zhang et al, 2017;Gao et al, 2018;Zhang et al, 2018;Zhang and Villarini, 2019;Gao et al, 2020). Besides the interannual variability, some studies have suggested a significant multidecadal change in the WNP TC activity (Leung et al, 2005;Chan, 2006;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Madden-Julian oscillation (MJO), Pacific-Japan (PJ) teleconnection and other atmospheric variabilities also play roles in influencing the WNP TC activity (Nakazawa 1986;Maloney and Hartmann 2001;Wu et al, 2020;Zhou et al, 2019). Some other studies highlighted the remote effects of SST variability in Indian and Atlantic Oceans on WNP TCs but mostly focused on the frequency and genesis of TCs (Liu and Chan, 2008;Liu and Chan, 2013;Huo et al, 2015;Zhang et al, 2017;Gao et al, 2018;Zhang et al, 2018;Zhang and Villarini, 2019;Gao et al, 2020). Besides the interannual variability, some studies have suggested a significant multidecadal change in the WNP TC activity (Leung et al, 2005;Chan, 2006;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Huang and Chan (2014) show that East China TC activity is the worst represented region in global hindcast data as well as having the lowest skill in dynamical downscaling forecasts. Yu et al (2017) find that TC frequency in South East China is linked with position the East Asian westerly jet, while (Gao et al, 2018(Gao et al, , 2020 found connections between tropical North Atlantic sea surface temperature (SST) and landfall activity in China.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al . (2017) find that TC frequency in South East China is linked with position the East Asian westerly jet, while (Gao et al ., 2018, 2020) found connections between tropical North Atlantic sea surface temperature (SST) and landfall activity in China.…”
Section: Introductionmentioning
confidence: 99%
“…As the most active area of tropical cyclones (TCs) in the world, the western North Pacific (WNP) generates an average of about 26 TCs annually, with about 12 TCs landing in the East Asia in the peak season (June to October) (Zhao et al, 2010;Gao et al, 2018;Gao et al, 2020b). The total population of East Asia accounts for about 25% of the world, most of which are concentrated in the southeast coast, such as the relatively developed South China.…”
Section: Introductionmentioning
confidence: 99%
“…La Niña in the central Pacific inhibits TC generation in the southeast of WNP (Zhang et al, 2012;Wang et al, 2013). In recent years, some studies have pointed out that there is also a close relationship between the tropical North Atlantic (TNA) SST and WNP TC generation activity (Yu et al, 2016;Zhang et al, 2017;Huo et al, 2015;Gao et al, 2018;Gao et al, 2020b). When the cold SST anomaly occurs in TNA, the relative humidity in the South China Sea will increase and the vertical wind shear in the east of WNP will be weakened, forming three anomaly-centers of TC generation frequency in WNP.…”
Section: Introductionmentioning
confidence: 99%